Hubungan Antara Efektivitas Fungsi Bimbingan dan Konseling Dengan Persepsi Siswa Terhadap Bimbingan dan Konseling di Sekolah Menengah Pertama Stella Duce I Yogyakarta - Kristianto Batuadji; Nuryati Atamimi; Rasimin B. Sanmustari (Jurnal Psikologi, 2009)
The aim of this istudy is to investigate the relationship between the effectiveness of guidance and counselling’s function and student’s perception towards guidance and counselling in Stella Duce I Middle School of Yogyakarta. It was hypothesized that there is a positive relationship between effectiveness of guidance and counselling’s function and student’s perception towards guidance and counselling. The subjects of this study (N = 117) were the students of Stella Duce I Middle School of Yogyakarta. Two questionnaires were applied to measure effectiveness of guidance and counselling’s function and student’s perception towards guidance and counselling. The result indicated a positive and significant relationship between effectiveness of guidance and counselling’s function and student’s perception towards guidance and counselling (r = 0,677 p = 0,000), meaning that the research hypothesis was accepted. The determination coefficient was 0,459 indicating that the effectiveness of guidance and counselling’s function contributes 45, 9% to the development of student’s perception towards guidance and coun‐selling.